PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP MINAT BELAJAR SISWA KELAS IV SD MUHAMMADIYAH HARJOWINANGUN - Ananda Saputra, Muhammad; Sumariyak, Asep (Universitas Negeri Medan, 2025)
Abstract: This study aims to examine the effect of contextual teaching and learning (CTL) on the learning interest of fourth-grade students at SD Muhammadiyah Harjowinangun in science subjects. The research used a pre-experimental one-group pretest-posttest design. Data collection techniques used interviews, questionnaires, and observation. The population was all fourth-grade students, and the research sample consisted of 22 fourth-grade students. Data analysis used a correlation test to determine the effect of the contextual learning model on student learning interest. The results showed a significant increase in students’ learning interest after applying the CTL model. Statistical analysis revealed a correlation coefficient of 0.600 with a significance value of 0.002, indicating a strong and significant influence. CTL is proven to be an effective model for enhancing student engagement and interest in science learning. Keyword: Contextual Teaching, Learning Interest Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kontekstual terhadap minat belajar siswa kelas IV SD Muhammadiyah Harjowinangun pada mata pelajaran IPA. Metode yang digunakan adalah pre-eksperimental design dengan one group pretest-posttest design. Teknik pengumpulan data menggunakan wawancara, angket dan observasi. Populasi seluruh siswa kelas IV dan sampel penelitian siswa kelas IV yang berjumlah 22 siswa. Teknik analisis data menggunakan uji korelasi untuk melihat pengaruh model pembelajaran kontekstual terhadap minat belajar siswa. Hasil penelitian menunjukkan adanya peningkatan minat belajar siswa setelah diterapkan model pembelajaran kontekstual. Berdasarkan hasil uji statistik, diperoleh nilai korelasi sebesar 0,600 dengan signifikansi 0,002 yang berarti terdapat pengaruh signifikan. Model pembelajaran kontekstual terbukti efektif dalam meningkatkan minat belajar siswa. Kata Kunci: Pembelajaran Kontekstual, Minat Belajar